The Combination of Pakcoy Juice (Brassica Rapa L.) and Antihypertensive Medication in Reducing Blood Pressure in Pregnant Women with Hypertension - Ardini, Weda Ayu; Irayani, Fahrul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Hypertension in pregnant women ranks as the second highest cause of Chronic Kidney Disease (CKD). Hypertension is defined as a minimum diastolic blood pressure of 90 mmHg and a minimum systolic blood pressure of 140 mmHg, with an increase in diastolic and systolic pressure of at least 15 mmHg and 30 mmHg, respectively. This study aims to evaluate the impact of a combination of Pakcoy juice (Brassica rapa L) and antihypertensive medication on blood pressure in pregnant women with hypertension.Using a quasi-experimental design with a One Group Pre-Test – Post-Test without a control group, the study involved 14 pregnant women with hypertension at the Gunung Sugih Community Health Center from January to June 2023 as the population. The results of data analysis indicate a significant influence (p value 0.000 < α: 0.05) on the reduction of blood pressure after the administration of antihypertensive medication and Pakcoy juice.The discussion emphasizes that Pakcoy juice is effective as a supplement to antihypertensive medication due to its natural content of potassium, calcium, and magnesium, which can reduce blood pressure. Consuming 4,700 milligrams of potassium per day is known to lower blood pressure caused by high sodium intake. In conclusion, the combination of Pakcoy juice and antihypertensive medication has a positive effect of 19% on reducing blood pressure in pregnant women with hypertension at the Gunung Sugih Community Health Center, with a recommendation for health education outreach to prevent hypertension cases in pregnant women.